The erosion of well-being in the digital age: a moderated mediation model of moral disengagement, internet addiction, and social support in adolescents - Fandy Achmad Yunian; Nuraeni .Nuraeni; Mohd Nazri Abdul Rahman; Mahdi Anbari (Jurnal Konseling dan Pendidikan, 2026)
The increase in adolescents’ digital activity poses serious psychological risks, as moral disengagement and internet addiction have the potential to erode adolescents’ well-being. This study examines a mediation-moderation model to understand the influence of moral disengagement on subjective well-being, with internet addiction as the mediator and social support as the moderator. Involving 271 high school students in Purwokerto selected through cluster random sampling, the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal a complex dynamic: although moral disengagement has a significant direct positive effect on subjective well-being suggesting a short-term defense mechanism to avoid internal moral sanctions this well-being is illusory. This is evidenced by the mediating role of internet addiction, which attenuates this positive effect; moral disengagement serves as a strong predictor of addictive behavior, which ultimately significantly reduces subjective well-being. Furthermore, the moderation hypothesis was rejected; social support failed to mitigate the negative impact of moral disengagement. Additional findings indicate that moral disengagement is negatively correlated with social support, suggesting the occurrence of a resource loss spiral in which immoral behavior erodes the social support that should serve as a protective buffer. Therefore, interventions for adolescent well-being cannot rely solely on strengthening external social support which has proven vulnerable to moral degradation but must prioritize moral cognitive restructuring and digital ethics literacy to break the cycle of addiction and prevent social isolation.